An Analysis of Finance Journal Impact Factors - Borokhovich, Kenneth A.; Bricker, Robert J.; Simkins, Betty J. (Journal of Finance, 2000)
This paper provides an analysis of the citation counts of articles published in the leading finance journals. It identifies the determinants of the most prevalent measure of influence for finance journals, the Social Sciences Citation Index impact factors. It finds that impact factors are affected by citations outside the finance field, are not affected by the distribution of published articles across subfields, and are good predictors of the long‐term citation counts of articles. The citation impact factors are reduced for both the Journal of Financial Economics and The Journal of Finance by their publication of other than regular articles.